CONNECTING WITH THE PAST, SHAPING THE FUTURE: THE POWER OF ORAL HISTORY - Blerta MUSTAFA; Zinaide GRUDA; Laura CRUZ (Езиков свят)
Oral history is an innovative approach that creates opportunities for students to learn about the world through inquiry, authentic and transformative learning. This study explores how using oral history as an effective pedagogical tool in an EFL context can transform student learning. Through experiential learning, undergraduate students of the English Language and Literature Department of the University of Prishtina interviewed community members, engaged with cultural, traditional and historical narratives and developed digital projects to document and preserve untold stories, which they then presented in front of an authentic audience at the annual student conference. Data collected through reflection papers, a focus group interview, and post conference insights reveal that students’ learning journey was marked by a “roller coaster” of emotions and multiple challenges, including adjusting to a new research approach, identifying suitable interviewees, and navigating the video editing techniques. Despite the challenges, students considered the project a rewarding experience, which helped them transform their learning and support their growth into active citizens. More importantly, through this experience, students not only grew academically but they also developed labor-marked competencies such as critical thinking, creativity, collaboration, digital literacy, communication, and linguistic and intercultural competencies. They also conveyed a great sense of pride, commitment and agency to safeguarding their country’s history, tradition and culture. These findings highlight the value of integrating oral history projects in transforming students’ learning experiences and in preparing them better for the challenges of the real world.